A SIMPLE AND RAPID LIQUID CHROMATOGRAPHY METHOD FOR DETERMINATION OF LEVOFLOXACIN IN PLASMA (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Introduction: Levofloxacin (LFX) is one of the second line anti-tuberculosis drugs used in the treatment of multi drug resistant tuberculosis. Monitoring of LFX concentrations in plasma may be valuable to study its pharmacokinetics and drug-drug interaction when co-administered with other anti-tuberculosis drugs. We developed a high performance liquid chromatic method of determination of LFX in plasma.Methodology: The method involved deproteinisation of the sample with perchloric acid and analysis of the supernatant using a reversed-phase C18 column (150mm) and fluorescence detection at an excitation wavelength of 290 nm and an emission wavelength of 460 nm.Results: The assay was specific for LFX and linear from 0.25 to 10.0μg/ml. The relative standard deviation of intra- and inter-day assays was lower than 10%. The average recovery of LFX from plasma was 99%.Conclusion: A sensitive, specific and validated method for quantitative determination of LFX in plasma was developed .Due to its simplicity; the assay can be used for pharmacokinetic studies of LFX.SAARC J TUBER LUNG DIS HIV/AIDS, 2017; XIV(1), page: 27-32